A contribution to the systematics of Neotropical Tanytarsus van der Wulp: first descriptions from Ecuador (Diptera: Chironomidae: Tanytarsini) - Giłka, Wojciech; Zakrzewska, Marta (Zootaxa, 2013)
First specific records of Tanytarsus van der Wulp from the Ecuadorian mainland based on detailed descriptions are presented. Tanytarsus cayambe sp. nov. shows an interesting set of characters known from several Neotropical Tanytarsus as well as from species of the recurvatus group of the northern distribution. Tanytarsus cotopaxi sp. nov. is placed in the riopreto species group; as a result an emended diagnosis for adult males of the group is proposed. The diagnostic description of Tanytarsus curvicristatus Contreras-Lichtenberg is also complemented.